Answer:
RTA= (x-2)·(x-11/2)/(x-2)(x-4)= (you can simplify again if you want by eliminating both (x-2)
(x-11/2)/(x-4)
Step-by-step explanation:
Ok we need to simplify the expression so:
x^2+3x-10= Bhaskara formula=
-3(±√9-4·1·(-10))/2·1=
X1=(-3+7/2)--> X1=2(R)---> (X-R)--->X-2
X2=(-3-7)/2 --> X2=11/2(R)---> (X-R)--->X-11/2
x^2-6x+8= Bhaskara formula=
6(±√36-4·1·8)/2·1=
X1=(6-2)/2=2--> X1=2(R)---> (X-R)--->X-2
X2=(6+2)/2=2--> X2=4(R)---> (X-R)--->X-4
so, The simplify expression is
(x-2)·(x-11/2)/(x-2)(x-4)=